12x5x-7 = 2x^-5 2x+4^= 4x^+5 3x-5^= 3x^-x+14 4 9x4x-1= 3x-1

1)2x(5x-7) = 2x^-5

 

2)(x+4)^= 4x^+5

 

3)(x-5)^= 3x^-x+14

 

4) 9x(4x-1)= 3x-1

  • 1)2x(5x-7) = 2x^-5

       10x²-14x-2x²+5=0

       8x²-14x+5=0

       D=b²-4ac=14²-4·8·5=196-160=36 , 2 корня

      x1=14+√36/16=14+6/16=20/16

      x2=14-6/16=8/16=1/2

    2)(x+4)^= 4x^+5

       x²+8x+16-4x²-5=0

       -3x²+8x+11=0  |·(-1)

       3x²-8x-11=0

        D=b²-4ac=(-8)²-4·3·(-11)=64+132=196 , 2 корня

       x1=8+√196/6=8+14/6=22/6=11/3

       x2=8-14/6=-6/6=-1

    3)(x-5)^= 3x^-x+14

    x²-10x+5²=3x²-x+14

    x²-10x+25-3x²+x-14=0

    -2x²-9x+11=0  |·(-1)

    2x²+9x-11=0 

    D=b²-4ac=9²-4·2·(-11)=81+88=169, 2 корня

    x1=-9+√169/4=-9+13/4=4/4=1

    x2=-9-13/4=-22/4=-5.5

    4) 9x(4x-1)= 3x-1

    36x²-9x-3x+1=0

    36x²-12x+1=0

    D=b²-4ac=(-12)²-4·36·1=144-144=0? 1корень

    x=12+0/36=12/36=1/3



See also: